Transformasi Keuangan Berkelanjutan: Peran Kebijakan Green Bond dan Indeks SDGs di ASEAN - Anisha Anisha; Panca Wijaya; Eogenie Lakilaki; Tri Wahyuni; Muhammad Dito Jastian Sidik; Alhafiz Alhafiz (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
This study delves into the dynamics of green bond issuance in ASEAN-5 (Indonesia, Malaysia, Singapore, the Philippines, and Thailand) and its key determinants, particularly green bond policies and the SDGs Index. Using secondary data from the IMF, World Bank, ADB, and financial reports, it applies panel data regression models (CEM, FEM, REM) for the 2016-2020 period with Chow, Hausman, and Lagrange Multiplier tests. The findings reveal that green bond policies have a significant positive impact, while the SDGs Index shows a weaker yet positive effect. Countries with robust regulations and market maturity, such as Singapore and Malaysia, have more advanced green bond markets than Indonesia and the Philippines, which face regulatory and financial literacy challenges. The study highlights the need for stricter regulations, greater transparency, and fiscal incentives to enhance investor participation, alongside improved green financial literacy to expand access to sustainable finance in ASEAN.